Clinical assessment of a new 755 nm diode laser for hair removal: Efficacy, safety and practicality in 56 patients. Issue 4 (19th December 2016) - Royo, Josefina; Moreno‐Moraga, Javier; Trelles, Mario A.
Abstract : Background and Objective: Recently, the first diode laser with a wavelength of 755 nm for in‐motion hair removal came on the market. The objective of this study was to check its efficacy, safety, and practicality under different options for its use. Methods: A prospective study in a heterogeneous group of 56 patients who had hair removed from various areas of their bodies using three different treatment methods. Four sessions were scheduled in all cases, with a gap of 3 months between each session. Efficacy was assessed by counting of hairs per cm 2 and the adverse effects in each session were recorded in detail in the patients' clinical histories. Results: The three tested options achieved a significant reduction in the number of hairs ( P < 0.0001). The average clearances achieved using the conventional method (HR), the in‐motion method (SHR) and the stacking method were 75.5%, 70.1%, and 41.9%, respectively. The degree of satisfaction of the participants on a scale of 0–10 was 7.7, 8.1 and 6.8, respectively. Erythema and perifollicular edema, which are characteristic responses in laser hair removal, were observed. The incidence of burns was 1.33%. Conclusion: The 755‐nm diode laser performed efficiently and safely in all the tested areas, using high total accumulated energy per surface unit. Based on our prior experience with other equipment, the results are promising. Lasers Surg. Med. 49:355–360, 2017. © 2016 Wiley Periodicals, Inc.